Experimental Investigation for Moment Redistribution in Continuous RC Beams Top Strengthened with CFRP and Steel Plates. Issue 1 (April 2020) - Ibrahim, Amr; Salem, Shady; Khalil, Ayman; El-Kateb, Mahmoud
Abstract: An experimental study was conducted on eight T-section continuous reinforced concrete beams top strengthened with CFRP and steel plates. The beams had a constant cross section and flexural steel reinforcement which was designed to prevent brittle failure due to crushing of concrete before steel yielding. The plates were installed on both sides of the slab above the beam web as near surface mounted or externally bonded to investigate the effect of different plating techniques on the moment redistribution in reinforced concrete beams. The number of plates in each specimen was changed. Steel stirrups were used and designed so that no premature shear failure occurs. The experimental results show that the steel plating can cause up to 40 % redistribution of moments from the sagging to the hogging regions compared to the control specimen as well as a significant increase in the loading capacity of the beams. The results also revealed that the application of CFRP plates can lead to substantial amounts of moment redistribution when they are installed as near surface mounted plates, but without enhancing the load carrying capacity.